CO2 fixation by anaerobic non-photosynthetic mixotrophy for improved carbon conversion - Shawn W. Jones (Nature Portfolio, 2016)
Microbial fermentation yield is limited by CO2 loss in glycolysis. Here, the authors engineered Clostridium ljungdahlii for the anaerobic, non-photosynthetic mixotrophy production of acetone, increasing carbon product yield while reducing CO2emissions from a biogenic feedstock fermentation.